PENGARUH MODAL SENDIRI DAN PENERIMAAN KREDIT TERHADAP PENDAPATAN PEDAGANG KECIL DI PASAR SIMPANG BARU PANAM PEKANBARU - harini, Nurfi harini Nurfi; Armas, Riadi Armas Riadi; ', Hardisem Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : What percentage of the influence of Equity and Acceptance Credit to Small Traders Revenue in Simpang Pasar Baru Panam Pekanbaru. This research was conducted in Pasar Baru Simpang Panam Pekanbaru in May-finished. The method used is descriptive quantitative method. The population in this study are all traders who trade in the market a new intersection panam pekanbaru totaling 320 traders and 10% of the population sampled is 32 respondents. The sampling based on purposive sampling. Data were collected through a questionnaire while analyzed using univariate and bivariate linear regression significant level of 0.05%. Based on the survey results revealed that the own capital and credit acceptance affect the income of traders, it is based on the results of the analysis using SPSS, showed simultannya calculation of F (9125)> F table (4.183) with Sig. (0.001) <0.05 while partially unknown variable tcount Equity (2,227)> t table (2.045) and Sig. (0,023) <0.05 and Credit Acceptance is known tcount (3,413)> t table (2.045) and Sig. (0.002) <0.05. So it can be concluded that there is significant influence from its own capital and acceptance of credit against the income of small traders in the market panam pekanbaru new intersection. The amount of contributions or donations of their own capital and acceptance of credit to traders income shown by the R Square of 0.386. What this means is that the contribution of the influence of their own capital and acceptance of credit againstincome amounted to 38.6% and the rest of 61.4% are not addressed in this studyKey words: influence, equity, credit receipts, income